Y-Chromosomal SNPs in Finno–Ugric-Speaking Populations Analyzed by Minisequencing on Microarrays - Raitio, Mirja; Lindroos, Katarina; Laukkanen, Minna; Pastinen, Tomi; Sistonen, Pertti; Sajantila, Antti; Syvänen, Ann-Christine (Genome Research, 2001)
An increasing number of single nucleotide polymorphisms (SNPs) on the Y chromosome are being identified. To utilize the full potential of the SNP markers in population genetic studies, new genotyping methods with high throughput are required. We describe a microarray system based on the minisequencing single nucleotide primer extension principle for multiplex genotyping of Y-chromosomal SNP markers. The system was applied for screening a panel of 25 Y-chromosomal SNPs in a unique collection of samples representing five Finno–Ugric populations. The specific minisequencing reaction provides 5-fold to infinite discrimination between the Y-chromosomal genotypes, and the microarray format of the system allows parallel and simultaneous analysis of large numbers of SNPs and samples. In addition to the SNP markers, five Y-chromosomal microsatellite loci were typed. Altogether 10,000 genotypes were generated to assess the genetic diversity in these population samples. Six of the 25 SNP markers (M9,Tat, SRY10831, M17, M12,92R7) were polymorphic in the analyzed populations, yielding six distinct SNP haplotypes. The microsatellite data were used to study the genetic structure of two major SNP haplotypes in the Finns and the Saami in more detail. We found that the most common haplotypes are shared between the Finns and the Saami, and that the SNP haplotypes show regional differences within the Finns and the Saami, which supports the hypothesis of two separate settlement waves to Finland.
10.1101/gr.156301